An Analysis on Hemocytes Profile in Kijing Taiwan (Anodonta woodiana) and Water Quality in Freshwater Aquaculture Ponds - Wijayanti, Dyah Ayu; Hertika, Asus Maizar Suryanto; Yanuwiadi, Bagyo (Graduate School, Universitas Brawijaya, 2018)
Kijing Taiwan (Anodonta woodiana) is found in water with muddy substrate. Kijing Taiwan lives in bottom waters and is relatively settled. Kijing Taiwan is a filter feeder organism that can filter water and is able to survive in polluted environment, so it can be used as a bio-indicator of a water body. The study was conducted in the Public Hatchery Unit (UPR) Sumber Mina Lestari. Profile hemocytes in Taiwan Kijing influenced by environment pollution inducer among others. Hemocytes were observed consisting of Total Haemocyte Count (THC) and Differential Haemocyte Count (DHC). The results show that the profile of hemocytes (THC and DHC) of Kijing Taiwan is not polluted. Results from aquaculture pond water quality measurements indicate that the indicators of the water quality i.e. temperature, pH, dissolved oxygen, and ammonia are still within normal limits. However, in TOM test, BOD and soil organic matter has exceeded the normal limits. The existence of organic matter became the medium of life for Kijing Taiwan, due to its role as a biofilter among other organic materials. Keywords: Hemocytes Profile, Kijing Taiwan, Water Quality.